Raiders, rulers, and traders : the horse and the rise of empires - Chaffetz, David (W.W. Norton & Company, 2024)
A captivating history of civilization that reveals the central role of the horse in culture, commerce, and conquest. No animal is so entangled in human history as the horse. The thread starts in prehistory, with a slight, shy animal, hunted for food. Domesticating the horse allowed early humans to settle the vast Eurasian steppe; later, their horses enabled new forms of warfare, encouraged long-distance trade routes, and ended up acquiring deep cultural and religious significance. Over time, horses came to power mighty empires in Iran, Afghanistan, China, India, and, later, Russia. Genghis Khan and the thirteenth-century Mongols offer the most famous example, but from ancient Assyria and Persia, to the seventeenth-century Mughals, to the high noon of colonialism in the early twentieth century, horse breeding was indispensable to conquest and statecraft.